SD Simulation Research on the Green Low-Carbon Development of Coal Enterprises - Yinna Xu; Guohao Zhao; Baojian Zhang; Jiao Jiao (Complexity, 2021)
The green low-carbon development system of enterprises, differing from the traditional linear system, is a nonlinear feedback system with complex causality. Based on self-organization theory, this study clarified the self-organization evolution logic of the green low-carbon development of coal enterprises and constructed a system dynamics model following a system dynamics method. Through a scenario simulation analysis, the impact of the market environment, environmental regulation, and enterprises’ innovation level on the green low-carbon development of coal enterprises was revealed. Applicability suggestions based on simulation results were proposed. The results confirmed that the main challenge for coal enterprises is that the coal market environment restricts the promotion of green low-carbon development level of coal enterprises. Improving innovation levels is the most effective way for coal enterprises to address these issues.